2011
DOI: 10.1152/ajpcell.00354.2010
|View full text |Cite
|
Sign up to set email alerts
|

Age-related impairment of T cell-induced skeletal muscle precursor cell function

Abstract: Sarcopenia is the age-associated loss of skeletal muscle mass and strength. Recent evidence suggests that an age-associated loss of muscle precursor cell (MPC) functionality contributes to sarcopenia. The objectives of the present study were to examine the influence of activated T cells on MPCs and determine whether an age-related defect in this signaling occurs. MPCs were collected from the gastrocnemius and plantaris of 3-mo-old (young) and 32-mo-old (old) animals. Splenic T cells were harvested using anti-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 72 publications
2
16
0
Order By: Relevance
“…The immune system responds to muscle damage with a complex sequence of immune reactions leading to recruitments of inflammatory and immune cells that ultimately lead to satellite cell activation, proliferation and eventually muscle regeneration. In the last decade, there has been a remarkable increase in the number of studies regarding the interaction of exercise and the immune system [10,15,30,31]. However, a role of the acquired immune system, in particular T-lymphocytes, in muscle function and performance has not been investigated, but needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune system responds to muscle damage with a complex sequence of immune reactions leading to recruitments of inflammatory and immune cells that ultimately lead to satellite cell activation, proliferation and eventually muscle regeneration. In the last decade, there has been a remarkable increase in the number of studies regarding the interaction of exercise and the immune system [10,15,30,31]. However, a role of the acquired immune system, in particular T-lymphocytes, in muscle function and performance has not been investigated, but needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…One study, using scid/mdx ( mdx : dystrophic mouse, scid : immunodeficient mouse) as model to examine possible interactions between skeletal muscle and T cells, demonstrated that these mice exhibited reduced muscle fibrosis and degeneration [14]. Recently, Dumke and Lees investigated the influence of activated T lymphocytes on the regeneration capacity of muscle precursor cells [15]. In this study, rat satellite cells were isolated from the gastrocnemius and plantaris muscles of 3 and 32 month old animals and were cultured with splenic activated T cells.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in general agreement with previous work. For example, there is evidence to suggest that MPCs obtained from elderly animals can proliferate and differentiate similarly to that of young animals (Dumke & Lees, 2011). Single fibre grafting experiments have shown that satellite cells from old animals possess an equivalent in vivo myogenic and self-renewal potential to that of young animals (Collins et al, 2007).…”
mentioning
confidence: 99%
“…Consequently, contraction‐ or trauma‐induced muscle damage accumulates while aging through cycles of insufficient regeneration (Conboy et al. ; Dumke and Lees ).…”
Section: Introductionmentioning
confidence: 99%
“…The failure to activate and proliferate satellite cells in older age is not necessarily only related to intrinsic deficits, but the microenvironment is also implicated (Dumke and Lees ; Barberi et al. ).…”
Section: Introductionmentioning
confidence: 99%